1976
DOI: 10.1111/j.1476-5381.1976.tb07659.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition by Glucagon of the Vasoconstrictor Actions of Noradrenaline, Angiotensin and Vasopressin on the Hepatic Arterial Vascular Bed of the Dog

Abstract: I The hepatic artery of the anaesthetized dog was cannulated and perfused from a femoral artery, the blood flow and perfusion pressure being monitored continuously. The sympathetic periarterial nerves were divided. 2 Dose-dependent increases in hepatic arterial vascular resistance (HAVR) resulted from intraarterial injections of noradrenaline, angiotensin and vasopressin. 3 Single injections of glucagon (100 gg, i.a.) caused a transient significant fall in HAVR of 19.9 + 3.2%, and infusions of 25 tg/min of glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 23 publications
3
27
0
Order By: Relevance
“…The consequent initial rise in calculated HAVR, indicating vasoconstriction, and the subsequent fall in calculated HAVR, indicating vasodilatation, were related to the dose of noradrenaline injected ( Figure 2) until doses in excess of 10 or 50 jig in different experiments were injected, when no secondary effect was apparent. The Richardson & Withrington, 1976a). The maximum secondary reduction in HAVR to noradrenaline of 16.0 + 2.4% was however significantly smaller than the maximum response to isoprenaline of 38.6 + 2.9% (P< 0.001) where maximum responses to both agents were established in the same 8 preparations.…”
Section: Assessment Ofdrug Effectsmentioning
confidence: 86%
See 1 more Smart Citation
“…The consequent initial rise in calculated HAVR, indicating vasoconstriction, and the subsequent fall in calculated HAVR, indicating vasodilatation, were related to the dose of noradrenaline injected ( Figure 2) until doses in excess of 10 or 50 jig in different experiments were injected, when no secondary effect was apparent. The Richardson & Withrington, 1976a). The maximum secondary reduction in HAVR to noradrenaline of 16.0 + 2.4% was however significantly smaller than the maximum response to isoprenaline of 38.6 + 2.9% (P< 0.001) where maximum responses to both agents were established in the same 8 preparations.…”
Section: Assessment Ofdrug Effectsmentioning
confidence: 86%
“…In order to demonstrate vasodilatation quantitatively in this vascular bed, it is necessary to retain the sympathetic innervation intact (Richardson & Withrington, 1976d;1977a); if the periarterial nerves accompanying the hepatic artery are sectioned, catecholamines injected intra-arterially cause only vasoconstriction (Richardson & Withrington, 1976a and unpublished observations); similarly, the administration of a-adrenoceptor antagonist drugs may reduce the hepatic arterial vasoconstrictor tone which is necessary for the quantitative examination of vasodilator responses.…”
Section: Introductionmentioning
confidence: 99%
“…These preparations have been described previously (arterial: Richardson & Withrington, 1976b;portal: Richardson & Withrington, 1977) (Bayliss, 1902;Folkow, 1964) are, in these preparations, negligible compared with the drug-induced changes in HAVR, whether vasoconstrictor (Richardson & Withrington, 1976a) or vasodilator (Richardson & Withrington, 1976b) (Levophed, Winthrop; mol. wt. of base = 169.0).…”
Section: Methodsmentioning
confidence: 99%
“…Vasopressin, whilst causing hepatic artery of the anaesthetized dog cause dose-profound dose-dependent vasoconstriction of the dependent hepatic arterial vasoconstriction (Andrews, hepatic arterial vascular bed (Richardson & Hecker, Maegraith & Ritchie, 1955;Richardson & Withrington, 1976a) has little effect on the resistance Withrington, 1976a); when administered by injection sites of the portal system except with very high doses into the hepatic portal vein they cause portal venous when it causes a reduction in portal vascular vasoconstriction although the responses to angio-resistance (Richardson & Withrington, 1977). tensin show marked tachyphylaxis (Richardson & Quantitative and qualitative differences in the responses of the hepatic arterial and portal vascular beds to naturally-occurring substances are therefore evident.…”
Section: Introductionmentioning
confidence: 99%
“…Sasaki et al (1985) reported that angiotensin II increased the concentration of arteriallyinfused krypton -81 m in both primary and metastatic liver tumours. This implies an increase in tumour blood flow relative to total hepatic arterial flow, but, as angiotensin II reduces hepatic arterial flow in the normal liver (Richardson & Witherington, 1976) All patients were studied at the time of placement of infusion catheters for regional delivery of chemotherapeutic drug to liver tumour. This study was approved by the hospital ethical committee, and all patients gave informed consent.…”
mentioning
confidence: 99%